An historical approach to the diagnostic biomarkers of acute coronary syndrome - Danese, Elisa (Ann Transl Med, 2016)
Suspected acute myocardial infarction (AMI) is one of the leading causes of admission to the emergency departments in Western countries but also an increasing cause in many other nations. The diagnosis of AMI involves the evaluation of clinical signs and symptoms, electrocardiographic assessment, and measurement of cardiac circulating biomarkers. In the last sixty years, the use of laboratory markers has changed considerably. Early biomarkers assessment has entailed testing for total enzyme activity of aspartate aminotransferase (AST), lactate dehydrogenase (LDH) and creatine kinase (CK). Advances in electrophoresis allowed the identification of more cardio-specific isoenzymes of both CK and LDH, thus leading to the introduction of the CK-MB and LDH-1 activity assays. Soon thereafter, the development of immunoassays, as well as technical advances in automation, allowed the measurements of the CK-MB in mass rather than in activity and myoglobin. Currently, cardiac troponins have the highest sensitivity and specificity for myocardial necrosis and represent the biochemical gold standard for diagnosing AMI. This review provides a chronology of the major events which marked the evolution of cardiac biomarkers testing and the development of the relative assays from the first introduction of AST in the 1950s to the last high sensitivity troponin immunoassays in the 2010s.